Blur and Fuzz: On Translating Representations of Low Resolution - Richard Shiff (Signata, 2016)
Digital photography and other electronic sources of representation generate images of such uniformly high resolution that the eye detects little transformation between the appearance of physical objects and their projected surrogates. With familiar signs of representational process and rhetoric screened out by these technologies, we find ourselves re-experiencing the anxiety of the early atomic age when humanists believed they had lost their place within a moral debate over progress in science. The scientists and even some philosophers were communicating through unvoiced mathematical symbols, not common words. It seemed then, as it may seem now, that abstract thinking had been cut loose from any foundation in the material world of physical being and feeling. With the transference of imagery from the miniature scale of cell phones to the grand scale of commercial digital projection—accomplished without apparent change in resolution—we lose the tension between our perception of the image and the materiality involved in its production. Nineteenth-century painting developed an uncomfortable rift between meaning and feel, between the projected image and the materiality of its representational basis. Contemporary work in many media—photography, film, video, computer electronics—continues to investigate the cognitive play of conceptual meaning and physical feel, but certain forms of painting continue to be the most effective. Paintings reveal factors of blur and fuzz that provide the sense of scale missing from digital projection. Blur and fuzz are experiential reminders of the arbitrary cultural codes in operation for the assessment of degrees of realism or truth in representation.